2x2-3x-5 = (2x-5)(x+1) when factored
3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)
The factors are -1(2x + 1)(3x + 4)
(x - 8)(3x + 4)
(2x - 5)(x + 1) or (2x + 5)(x - 1) depending on the sign of the term 3x
x(3x - 2)
6x2 + 10x = 2x*(3x + 5)
(3x + 1)(x - 5)
3x(2x + 1)
2x2-3x-5 = (2x-5)(x+1) when factored
(3x + 4)(2x - 1)
(x - 1)(3x + 5)
(x - 2)(2x + 7)
6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)
(x + 3)(3x - 2)
3X2 - 123(X2 - 4)=========All the factoring that can be done here.
6x3 + 9x2 - 2x2 - 3x Before any grouping, take out the common factor, x, to give x*(6x2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)